2019
DOI: 10.1097/mat.0000000000000895
|View full text |Cite
|
Sign up to set email alerts
|

Yellow Means Caution: Correlations Between Liver Injury and Mortality with the Use of VA-ECMO

Abstract: Abnormalities in markers of liver injury after venoarterial extracorporeal membrane oxygenation (VA-ECMO) initiation are of unclear distribution and clinical significance. This study included all consecutive adult patients from a single institution who underwent VA-ECMO cannulation between May 2012 and September 2016 and had liver function panels drawn during their admission (n = 223). Data points include: age, sex, body mass index, diagnosis, duration of ECMO cannulation, duration of hospitalization, pre-ECMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…A retrospective institutional database query found that the relevant parameters of liver function are usually normal before VA-ECMO initiation, but abnormalities in various markers develop after ECMO initiation. Finally, both bilirubin and lactate elevations correlated with increased mortality (22). Using a quantitative model, we definitively demonstrate that hyperbilirubinemia after ECMO initiation is a dominant factor in decreased survival and establish 65 µmol/L as the best cutoff value.…”
Section: Discussionmentioning
confidence: 66%
“…A retrospective institutional database query found that the relevant parameters of liver function are usually normal before VA-ECMO initiation, but abnormalities in various markers develop after ECMO initiation. Finally, both bilirubin and lactate elevations correlated with increased mortality (22). Using a quantitative model, we definitively demonstrate that hyperbilirubinemia after ECMO initiation is a dominant factor in decreased survival and establish 65 µmol/L as the best cutoff value.…”
Section: Discussionmentioning
confidence: 66%
“…Liver failure as an independent risk factor for mortality has previously not been described in larger studies and is supported by only limited literature regarding this topic. Altered liver parameters during ECLS therapy are known (27). The MELD-XI score is predictive of mortality in ECLS (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these authors used different definitions of renal failure. Masha et al defined acute renal failure as serum creatinine increase of more than 1.5 mg/dl with or without renal replacement therapy [36]; Rubino et al as renal impairment requiring continuous renal replacement therapy [37]; and Zhigalov et al as a new renal dysfunction requiring renal replacement therapy or a rise in serum creatinine (greater than three times baseline or greater than 5 mg/dL) [23]. Other authors defined renal failure as an acute kidney injury or organ dysfunction, failing to provide a more detailed definition [35,[38][39][40].…”
Section: Complications and Adverse Events During Va-ecmomentioning
confidence: 99%